The Role of Flash Sales and Joy of Missing Out (JOMO) in Shaping Impulsive Buying Behavior of E-Commerce Consumers in Cirebon City - Revasanda, Lameina; Fatimah , Siska Ernawati (Journal Research of Social Science, Economics, and Management, 2026)
Customers are now more exposed to time-based advertising tactics due to the rapid development of e-commerce and digital payment systems, which can exacerbate impulsive buying. This study uses the Stimulus-Response (S-R) theoretical framework to investigate how flash sales and the Joy of Missing Out (JOMO) influence impulsive buying among e-commerce customers in Cirebon City. While JOMO is an internal psychological stimulus that influences consumer reactions, flash sales are considered an external advertising stimulus. This study uses a quantitative methodology, collecting data through an online survey of 180 participants. The data was analyzed using Structural Equation Modeling with Partial Least Squares (SEMPLS). The results show that limited-time promotions increase emotional arousal and purchase urgency, as flash sales have a beneficial and significant impact on impulsive purchases. Conversely, impulsive purchase is negatively impacted by JOMO (Joy of Missing Out), suggesting that increased psychological awareness and self-control reduce the propensity for impulsive purchasing. Concurrently, impulsive purchasing is strongly influenced by flash sales and JOMO, underscoring the interaction between internal psychological control and external advertising pressure. The significance of digital marketing strategies that consider both customer psychological control and promotion intensity. In the context of a cashless digital economy, this study advances the use of stimulus-response theory to explain impulsive purchasing behavior.